Analysis Stock Price: Earnings per Share as Moderating Variable - Wicaksono, Fajrin; Aminah, Mina Siti; Sopiani, Lia; Mardiyani, Mardiyani (International Journal of Business, Economics, and Social Development, 2024)
This study seeks to determine the influence of moderating factors on the company's financial performance on the stock price in the consumer cyclical sector, such as current ratio, debt-to-equity ratio, return on equity, and earnings per share. The study's population consisted of industrial enterprises in the consumer cyclical sector sourced from the 2020–2022 Indonesia Stock Exchange website. Purposive sampling was used to acquire 31 firms for the study. Multiple regression and moderate regression analyses are data analysis procedures where Stata 17 software is used for data processing. Furthermore, this analysis assumes that the debt-to-equity ratio, return on equity, and current ratio affect stock prices. The debt-to-equity ratio, return on equity, and current ratio are all impacted by earnings per share. Stock prices might be impacted by it as well. Data analysis indicates that although the debt-to-equity and current ratios do not affect stock prices, the return on equity does. If profits per share rise, stock prices may be less impacted by debt-to-equity and current ratios. Earnings per share cannot moderate the Return on Equity on stock prices.